Optofluidic Switching of Nanoparticles Based on a WDM Tree Splitter - Wenxiang Jiao; Guanghui Wang; Zhoufeng Ying; Zhiwen Kang; Tianyu Sun; Ningmu Zou; Ho-pui Ho; Xuping Zhang (IEEE Photonics Journal, 2016)
We demonstrate a silicon-based wavelength-division multiplexing (WDM) tree splitter for optofluidic switching of nanoparticles in a lab-on-a-chip or nanofluidic system. The gradient force and scattering force induced by the evanescent field can, respectively, lead to trapping and transportation of colloidal polystyrene (PS) spheres directly above the waveguide. Guiding of PS into any designated branch within a cascaded tree splitter is achieved by switching of the excitation wavelength. As compared to that based on microrings, an optimized design of the reported tree splitter approach offers a number of advantages in terms of device compactness, wavelength tolerance, response speed, and trap stability, while maintaining the inherent low-loss and low-power performance features of WDM splitters. A network of such splitters can readily lead to a platform for high-throughput and large-scale particle manipulation in nanofluidic systems.